Foliar elementome and functional traits relationships identify tree species niche in F rench G uiana rainforests - Jordi Sardans; Joan Llusià; Romà Ogaya; Helen Vallicrosa; Iolanda Filella; Albert Gargallo‐Garriga; Guille Peguero; Leandro Van Langenhove; Lore T. Verryckt; Clément Stahl; Elodie A. Courtois; Laëtitia M. Bréchet; et al. (Ecology, 2023)
Biogeochemical niche (BN) hypothesis aims to relate species/genotype elemental composition with its niche based on the fact that different elements are involved differentially in distinct plant functions. We here test the BN hypothesis through the analysis of the 10 foliar elemental concentrations and 20 functional‐morphological of 60 tree species in a French Guiana tropical forest. We observed strong legacy (phylogenic + species) signals in the species‐specific foliar elemental composition (elementome) and, for the first time, provide empirical evidence for a relationship between species‐specific foliar elementome and functional traits. Our study thus supports the BN hypothesis and confirms the general niche segregation process through which the species‐specific use of bio‐elements drives the high levels of α‐diversity in this tropical forest. We show that the simple analysis of foliar elementomes may be used to test for BNs of co‐occurring species in highly diverse ecosystems, such as tropical rainforests. Although cause and effect mechanisms of leaf functional and morphological traits in species‐specific use of bio‐elements require confirmation, we posit the hypothesis that divergences in functional‐morphological niches and species‐specific biogeochemical use are likely to have co‐evolved.